DFT Investigation of CH4 and H2O Adsorption on Pd (111), Ni (111), Pt (111), and Ir(111) Surfaces - Onimisi Ibrahim, Abdulrauf; Jibril El-Yakubu, Baba (Journal of Science and Technology, 2023)
Using density functional theory (DFT) calculations, the surface Gibbs free energy of methane and water adsorption on Pt(111), Ir(111), Ni(111), and Pd(111) surfaces was investigated. DFT computations were employed to investigate the adsorption of methane and water molecule on unit cells with varying coverage levels of 0.11, 0.25, 0.50, and 1.00 monolayers and the aggregation of H2O over clean transition metal surfaces. The adsorption configuration was assessed to experimental findings to evaluate our computational approaches’ accuracy and reliability. A thermodynamic diagram was constructed for exploring the adsorption of CH4 and H2O on metal surfaces. The order of the methane adsorption energies on different metal surfaces is as follows: Pd(111) > Pt(111) > Ni(111) > Ir(111). A more significant number of H2O molecules on the transition metal surfaces reduces the contact between the metal surfaces and water molecules during water aggregation. The thermodynamic stability of water and methane adsorption coverage was found to be best on the Pt(111) surface.